2019
DOI: 10.1038/s41598-019-54847-y
|View full text |Cite|
|
Sign up to set email alerts
|

Escherichia coli and Salmonella Enteritidis dual-species biofilms: interspecies interactions and antibiofilm efficacy of phages

Abstract: Escherichia coli and Salmonella Enteritidis are foodborne pathogens forming challenging biofilms that contribute to their virulence, antimicrobial resistance, and survival on surfaces. Interspecies interactions occur between species in mixed biofilms promoting different outcomes to each species. Here we describe the interactions between E. coli and S. Enteritidis strains, and their control using specific phages. Single-species biofilms presented more cells compared to dual-species biofilms. The spatial organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…Antibiofilm activity assay. The effect of PHB19 and Dep6 on E. coli biofilms was assessed with 96-well microtiter plates or individual polystyrene plates as described previously (45)(46)(47). Briefly, E. coli biofilms were allowed to form in 96-well microtiter plates for 24 or 48 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiofilm activity assay. The effect of PHB19 and Dep6 on E. coli biofilms was assessed with 96-well microtiter plates or individual polystyrene plates as described previously (45)(46)(47). Briefly, E. coli biofilms were allowed to form in 96-well microtiter plates for 24 or 48 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Oxaran et al ( 27 ) interchanged L. monocytogenes and Staphylococcus aureus with each of their associated environmental spoilage microbiota communities and concluded that enhanced protection is caused by associations in the biofilm instead of specific characteristics of the pathogen. In addition, the decreased diffusion of antimicrobial agents through multilayer complex structures has been shown to contribute to the increased resistance ( 32 , 34 , 37 ). A dense structure of multiple heterogeneous layers of L. monocytogenes and Lactobacillus plantarum cells increased sanitizer tolerance of both species against benzalkonium chloride, but the protective effect was less pronounced against peracetic acid ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, similar to planktonic cells, the response of the bio lm to the phage was strain-dependent; the temperate phage ΦPan70 produced a reduction of 99.9% to ~ 99.999% depending on the strain [8]. Although the mechanism of phage-bio lm interaction is still unclear, it is believed that phage-derived enzymes degrade the major exopolysaccharide protective layer of the bio lm matrix, and consequently, phages can reach and kill bacterial cells in the bio lm [9]. Furthermore, phages can diffuse through the pores and channels in the bio lm to reach different layers of the bio lm [10].…”
Section: Discussionmentioning
confidence: 99%
“…For thermo-stability, the phage was incubated at 40 ºC, 50 ºC, 60 ºC, 70 ºC, and 80 ºC, and sample were collected after 20, 40, and 60 min for phage titration using the DLA method. For pH stability, the phage were added to tubes containing SM buffer of different pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and then incubated for 1 h at 37 ºC before phage titration was performed by the DLA method [17].…”
Section: Thermal and Ph Stabilitymentioning
confidence: 99%